Letting go - Stoeke, Janet Morgan (Stoeke, Janet Morgan. Loopy Coop hens., 2013)
Pip, Midge, and Dot are enjoying the shade under an apple tree when fruit starts falling around them, causing the hens to suspect a fox is in the tree trying to hit them.